Rancang Bangun Sistem Informasi Pada CV. Prayitno Rusni Creative Bagian Percetakan - Paisal Paisal (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2020)
Prayitno Rusni Creative Printing Section is a business entity that is engaged in printing that is trying to develop its business that its printing ordering service is still manual to become computerized. The problem faced by this business entity is the process of providing printing information that has not been real time, both between sections in the CV. Prayitno Rusni Creative, CV. Prayitno Rusni Creative with suppliers and CV. Prayitno Rusni Creative with distributors. It is expected that the information system for ordering at. CV Prayitno Rusni Creative can help manage information needed by consumers and in real time delivery, on time and strengthen the relationship between CV. Prayitno Rusni Creative with consumers and suppliers. For ordering information on the information system CV. Prayitno Rusni Creative includes: supplier data collection, suppliers, ordering. Hopefully with this information system CV. Prayitno Rusni Creative Printing Section is getting more and more consumers